Ruggero Jacobbi Prose e racconti - Inediti e rari - Fantacci, Silvia (Fonti storiche e letterarie - Edizioni cartacee e digitali, 2007)
Ah, if only I were not so alive and so crowded with things, what a book I would write [...] but there's so little time [...]. There's lots of time to map them out, that's true, but it's not enough. This is the voice of the protagonist of Convalescenza, one of the stories in this book that - thanks to the painstaking editorial attention of Silvia Fantacci - presents the prose written by Ruggero Jacobbi starting from his precocious youth through to the Sixties. The nine sections, recording fragments of memories, vestiges of mystery and bitter solitude, meander between cinema and theatre, revoke the faces of the war, recall the figures of writers and friends, suggest new approaches to reading. The evocation of Brazil, where Jacobbi spent the most important fifteen years of his life, is not lacking: a country "so big as to drive you crazy" with its magical rites, its rhythm, its culture (the music of Villa-Lobos, Vinícius de Morais and Dorival Caymmi and the poetry of his friend Murilo Mendes). The meticulous notes and the appendix at the end of the book illustrate the history of each text and offer a reconstruction of the projects for novels and stories that were left unfinished and have now finally been transferred from the mind and desk of the writer into book form.